حول أسلوب تحليل التغاير المتعدد باستخدام تصميم قطع منشقة - مهدي, دجلة ابراهيم (Journal of Economics and Administrative Sciences, 2010)
Analysis of Covariance consider to be quite important procedure to reduce the effect of some independents factors before going through the experiment. By this procedure we can compare variances causes from the difference between treatments and error term variance of they are equals or less than consider to be not significant, otherwise if is significant. We carry on with this comparison until we find the greatest covser for the significant variance flam the treatments. There are methods can be used like least significant difference method, Duncan method and Turkeys' w-procedure and Student Newman. Key Word: Analysis of variation; Split plot design; Repeated                       Measurements.